Pelatihan Pengembangan Pariwisata Kuliner Melalui Media Sosial Pada UMKM - Hastuti, Hastuti; Zayana, Zayana; Ahmad Bully, Nurlina; Kartika Putri, Ika (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2022)
Culinary tourism has become a potential sector in the Indonesian economy, especially in Baubau City. However, the development of technology and social media advances has made Micro, Small, and Medium Enterprises (MSMEs) have to have skills in utilizing social media to promote their culinary products. Training on culinary tourism development through social media is one way to improve the quality and competitiveness of MSME culinary products in Baubau City. Effective training methods can be carried out through practical and classroom training conducted by experienced and skilled instructors. Training materials can include effective marketing strategies through social media, techniques for taking attractive food photos, and basic concepts of marketing through social media. The benefits obtained by MSMEs after attending the training include improving the quality and competitiveness of products, the ability to use social media for promotion, and developing marketing networks. Training on culinary tourism development through social media can provide a positive contribution to improving the Indonesian economy, especially in Baubau City.